Methodical approaches to forecasting and early detection of economic cyclicity - Stetsenko, Sergii; Moholivets , Anton (Ways to Improve Construction Efficiency, 2021)
The analysis and generalization of theoretical preconditions of formation of the advancing economic indicators which at different times in different countries of the world are used as indicators of change of a phase of an economic cycle is carried out. Based on the analysis of literature sources, it is established that the methodology of economic forecasting of cyclicality in the scientific literature includes two main areas, namely: a) direct forecasting of the dynamics of key macroeconomic indicators based on extrapolation, correlation and regression analysis, expert surveys (consensus forecasts) and surveys of economic entities; b) the use of leading economic indicators, which by their nature can be pro-cyclical, counter-cyclical and acyclical, and in relation to the phase of the economic cycle - ahead, late and synchronous. The most common leading indicators are considered, among which the Index of leading economic indicators of the USA, Composite leading index of the Organization for Economic Cooperation and Development (OECD), Indicator of business confidence by types of economic activity, consumer confidence, business climate and economic sentiment in accordance with the Special Data Dissemination Standard of the International Monetary Fund. Since 2006, the National Bank of Ukraine has been conducting a survey on the status and prospects of business activity, and similar quarterly indicators have been developed by the State Statistics Service of Ukraine and implemented since 2013. At the same time, a separate indicator is proposed for forecasting business activity in construction - the indicator of business confidence in construction (IDVB). However, the feasibility of using these indicators has yet to be proven in practice. To increase the accuracy of forecasting changes in the phases of economic cycles, it is proposed to develop separate indicators at the sectoral and regional levels. Theoretical generalization and substantiation of causes, consequences, methods of counteracting economic cyclicality should become the basis for further applied research. This approach is a theoretical basis for the development of tools for countercyclical management of enterprises, sectors of the economy and national economies in conditions of fluctuations in business activity.